2013
DOI: 10.4103/0022-3859.123147
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delirium and inpatient mortality with delirium

Abstract: Age and use of restraints appears to be an important predictor mortality in patients with delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…Delirium is a critical mental status and a significant predictor of mortality. 39 Therefore, high mortality rates within the first month following antipsychotic prescription, particularly in the haloperidol group, can be attributed to the preexisting physical morbidities rather than the toxicity or adverse effects of the prescribed medications in the patients. In this study, a nonsignificant difference in the mortality risk was observed between the haloperidol and chlorpromazine groups at 90 days following prescription, indicating that if patients prescribed antipsychotic medications in urgent situations (ie, short-term and midterm uses) are excluded, the mortality risk of the haloperidol group was not particularly high.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is a critical mental status and a significant predictor of mortality. 39 Therefore, high mortality rates within the first month following antipsychotic prescription, particularly in the haloperidol group, can be attributed to the preexisting physical morbidities rather than the toxicity or adverse effects of the prescribed medications in the patients. In this study, a nonsignificant difference in the mortality risk was observed between the haloperidol and chlorpromazine groups at 90 days following prescription, indicating that if patients prescribed antipsychotic medications in urgent situations (ie, short-term and midterm uses) are excluded, the mortality risk of the haloperidol group was not particularly high.…”
Section: Discussionmentioning
confidence: 99%
“…This form aims to evaluate the risk factors related to delirium in patients and was prepared by the researcher based on the review of the respective literature and includes mostly the evidence‐level results (Barr et al., ; Celis‐ Rodriguez et al., ; van Diapen et al., ; Grover et al., ; Guenther et al., ; McPherson et al., ; Öztürk Birge & Tel Aydın, ; Pauley et al., ; Sato et al., ; Zhu et al., ). The delirium‐related risk factors evaluated in the form include any hearing and visual problems, the presence of invasive procedures such as central venous catheter, bladder catheter and NG/TPN, history of smoking and alcohol usage, the presence of hypoxia (SPO 2 < 90), hypo/hyperglycaemia (<70 or >200 mg/dl), hypo/hypernatremia (<135 or >145 mEq/L), hypo/hyperthermia (<36 or >38°C), Blood–Urea–Nitrogen/Creatinine (BUN/Cre) ≥18, anaemia (Hgb < 12 g/dl), hypoalbuminemia (Alb < 3.5 g/dl) and C‐reactive protein (CRP) >5 mg/dl.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to restraint use, van der Kooi et al (2015) reported that one of the reasons for physical restraint use in the ICU of Dutch hospital was delirium. Grover et al (2013) supported this fmding and further reported that physical restraint was a significant predictor of mortality for patients 65 years and older.…”
Section: Difficulty In Identification and Current Managementsupporting
confidence: 58%